New Cancer Immunotherapy Agents in Development: a report from an associated program of the 31stAnnual Meeting of the Society for Immunotherapy of Cancer, 2016. Issue 1 (20th June 2017) - Adusumilli, Prasad S.; Cha, Edward; Cornfeld, Mark; Davis, Thomas; Diab, Adi; Dubensky, Thomas W.; Evans, Elizabeth; Grogan, Jane L.; Irving, Bryan A.; Leidner, Rom S.; Olwill, Shane A.; Soon-Shiong, Patrick; et al.
Abstract : This report is a summary of 'New Cancer Immunotherapy Agents in Development' program, which took place in association with the 31st Annual Meeting of the Society for Immunotherapy of Cancer (SITC), on November 9, 2016 in National Harbor, Maryland. Presenters gave brief overviews of emerging clinical and pre-clinical immune-based agents and combinations, before participating in an extended panel discussion with multidisciplinary leaders, including members of the FDA, leading academic institutions and industrial drug developers, to consider topics relevant to the future of cancer immunotherapy.